2015
DOI: 10.1007/s00723-015-0699-7
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic Effects in NMR of New Prospective Water-Soluble Ligands SeP(CH2OH)3 and H[Se2P(CH2OH)2]

Abstract: We present the synthesis of new phosphine selenide SeP(CH 2 OH) 3 and diselenophosphinate H[Se 2 P(CH 2 OH) 2 ] and their characterization with nuclear magnetic resonance (NMR) spectroscopy and quantum chemistry methods. DFT calculations show large relativistic spin-orbit effects in NMR shielding of phosphorus nuclei. We discuss the impact of Se lone pairs and electrons of P-Se and P-C bonds on the 31 P NMR shift and, especially, its relativistic part. The description of P-Se bonds and characterization of elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…The SO-HALA effects in heavy chalcogen compounds have been well investigated, at least partly because the favorable spin 1/2 of 77 Se and 125 Te nuclei give rise to experimental multinuclear NMR studies that frequently also include the lighter nuclei. Relativistic effects on the NMR chemical shifts in heavy chalcogen compounds have been studied mostly by relativistic DFT methods. ,, Generally, the SO-HALA shielding increases uniformly with Z HA down group 16 and also increases with the number of occupied LPs at the HA, i.e, for a lower HA oxidation state. Maximal SO-HALA shieldings (>50 ppm) are reached for the heavier chalcogen compounds (Se and Te) in oxidation state – II, when a double bond to the LA is present (as in seleno- and telluroketones). ,, This bonding situation clearly favors the propagation of the SO-HALA effects from the HA to the LA in p-block species and additionally involves small energy denominators.…”
Section: Trends In So-hala Shifts Across the Periodic Tablementioning
confidence: 99%
“…The SO-HALA effects in heavy chalcogen compounds have been well investigated, at least partly because the favorable spin 1/2 of 77 Se and 125 Te nuclei give rise to experimental multinuclear NMR studies that frequently also include the lighter nuclei. Relativistic effects on the NMR chemical shifts in heavy chalcogen compounds have been studied mostly by relativistic DFT methods. ,, Generally, the SO-HALA shielding increases uniformly with Z HA down group 16 and also increases with the number of occupied LPs at the HA, i.e, for a lower HA oxidation state. Maximal SO-HALA shieldings (>50 ppm) are reached for the heavier chalcogen compounds (Se and Te) in oxidation state – II, when a double bond to the LA is present (as in seleno- and telluroketones). ,, This bonding situation clearly favors the propagation of the SO-HALA effects from the HA to the LA in p-block species and additionally involves small energy denominators.…”
Section: Trends In So-hala Shifts Across the Periodic Tablementioning
confidence: 99%
“…When applied to C 2 H 2 X 2 (where X = F, Cl, Br, or I), NBO/NLMO analysis of nuclear shielding confirms that NHD in these systems comes mostly from the spin–orbit HALA effect and also explains some steric effects on nuclear shielding in different isomers . Additionally, this procedure has been successfully applied to explain relativistic effects of some selenide phosphines in NMR . A comprehensive NBO/NLMO analysis of nuclear shielding was also carried out for IHD in the series of LaX3 complexes where X = F, Cl, Br, or I and showed that both the paramagnetic and SO deshielding terms increase with the number of the halogen, with the paramagnetic term being significantly larger than the SO term.…”
Section: Computational Details and Methodologymentioning
confidence: 99%
“…10 Additionally, this procedure has been successfully applied to explain relativistic effects of some selenide phosphines in NMR. 34 A comprehensive NBO/ NLMO analysis of nuclear shielding was also carried out for IHD in the series of LaX3 complexes where X = F, Cl, Br, or I 14 and showed that both the paramagnetic and SO deshielding terms increase with the number of the halogen, with the paramagnetic term being significantly larger than the SO term. As for the NHD in transition-metal complexes, one of the earliest works on NBO/NLMO analysis of nuclear shielding 13 was devoted to the explanation of nuclear shielding in various chloride and bromide Pt compounds.…”
Section: ■ Computational Details and Methodologymentioning
confidence: 99%